Riscos associados à água destinada ao consumo humano e as vulnerabilidades das populações urbanas - Luis Henrique Batista Gois (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2015)
O  s e r  h u m a n o  s e  e n c o n t r a  e x p o s t o  a  d i v e r s o s  t i p o s  d e  r i s c os  c o m  r e c o n h e c i d o s  e f e i t o s  à  s a ú d e . O s  r i s c o s  à  s a ú d e  a s s o c i a d o s  a o  c o n s u m o  d e  á g u a  p o d e m  r e p r e s e n t a r  d i v e r s o s  a g r a -v a n t e s  p a r a  o  q u a d r o  d e  m o r b i - m o r t a l i d a d e  d a  p o p u l a ç ã o. A  d i s t r i b u i ç ã o  d e s s e s  r i s c o s  s e  c o n c e n t r a  e m  t o d a s  a s  f o rm a s  d e  a b a s t e c i m e n t o  e  o s  m a i s  f r e q u e n t e s  e s t ã o  r e l a c i o n a- d o s  c o m  a  u t i l i za ç ã o  d e  á g u a  e m  q u a n t i d a d e  e  q u a l i d a d e  i n a- d e q u a d a s . A  v u l n e r a b i l i d a d e  d a  p o p u l a ç ã o  d i a n t e  d e  s i t u aç õ e s  d e  r i s c o  d e p e n d e , d e n t r e  o u t r o s  f a t o r e s , d e  c a r a c t e r í st i c a s  d a  p o p u l a ç ã o  e  d o s  r e c u r s o s  d i s p o n í v e i s  p a r a  o  e n f r e n t a m e n t o  e  c o n t r o l e  d o s  r i s c o s . E s s a  d i s s e r t a ç ã o  o b j e t i- v o u  e s t u d a r  o s  r i s c o s  a s s o c i a d o s  à  á g u a  d e s t i n a d a  a o  c o n s u m o  h u m a n o  e  a s  v u l n e r a b i l i d a d e s  d a s  p o p u l a ç õ e s  u r b an as.  A  m e t o d o l o g i a  s e  b a s e o u  n u m a  r e v i s ã o  b i b l i o g r á f i c a p a r a  s e l e ç ã o  d e  f a t o r e s  d e  r i s c o  e  v u l n e r a b i l i d a d e  e  d a  a p l i c a ç ã o  d o m é t o d o  D e l p h i , c o m  6 5  p a i n e l i s t a s  n a  p r i m e i ra  r o d a d a  e  4 2  n a  s e g u n d a , q u e  o b j e t i v o u  a  s e l e ç ã o  d e  u m  c o n j u n t o  d e  f a t o r e s  d e  r i s c o  e  v u l n e r a b i l i d a d e s  a s s o c i a d o s   à á g u a  p a r a  c o n s u m o  h u m a n o . C o m o  r e s u l t a d o  s e  o b t e v e  u m c o n j u n t o  d e  f a t o r e s  d e  r i s c o s  e  v u l n e r a b i l i d a d e  a s s o c i a d os a o  t i p o  d e  a b a s t e c i m e n t o  d e  á g u a , q u a l i d a d e  d a  á g u a  e  a  q u e s t õ e s  r e l a c i o n a d a s  c o m  a s  i n s t a l a ç õ e s  h i d r á u l i c a s  d o s d o m i c í l i o s . F o i  e l a b o r a d o  u m  q u a d r o  s í n t e s e  o n d e  é  a n a l is a d o  a  i n f l u ê n c i a  d e s s e s  f a t o r e s  e  a s  a ç õ e s  n e c e s s á r i a s  p ar a  g a r a n t i r  u m  c o n s u m o  d e  á g u a  s e g u r o . O s  r i s c o s  d i s c u t i d o s  p o r  e s s a  p e s q u i s a  p r e c i s a m  s e r  e n c a r a d o s  d e  f o r m a  m ais  o b j e t i v a  p e l o s  r e s p o n s á v e i s  p e l o  s e u  c o n t r o l e , u m a  v ez q u e  p o d e m  r e p r e s e n t a r  d a n o s  r e a i s  a  s a ú d e  d a  p o p u l a ç ã o  c o n s u m i d o r a . E s t e  c o n t r o l e  d e v e  s e r  c o n t í n u o  e  t e m  d e  c o nt e m p l a r  t o d a s  a s  e t a p a s  d o  a b a s t e c i m e n t o  d e  á g u a . O s  f a t or e s  p a r a  r e d u ç ã o  d a  v u l n e r a b i l i d a d e  d a  p o p u l a ç ã o  d i a n t e  d o s  r i s c o s  d e v e m  e s t a r  b a s e a d o s  n a  a ç ã o  c o n j u n t a  p r o m o v i d a  p e l o  f o r n e c e d o r  d a  á g u a , a u t o r i d a d e s  d e  s a ú d e  e  p e l o  p r ó p r i o  c o n s u m i d o r . R i s c o s  e  v u l n e r a b i l i d a d e s  d e v e m  s e r a n a l i s a d o s  n o  c o n t e x t o  r e a l  a o  q u a l  s e  i n s e r e m . P a r a  t a n t o é  n e c e s s á r i o  a  r e a l i za ç ã o  d e  e s t u d o s  q u e  v e r i f i q u e m  su a s  c o n s e q u ê n c i a s  p a r a  a  s a ú d e  e  b e m - e s t a r  d a  p o p u l a ç ã o , a v a -l i a n d o  t a m b é m  a  e x i s t ê n c i a  d e  i m p l i c a ç õ e s  n e g a t i v a s  e i d e n t i f i c a n d o  e  p r o m o ve n d o  m e c a n i s m o s  e f i c i e n t e s  q u e  g a- r a n t a m  u m  c o n s u m o  d e  á g u a  s e g u r o .